Cross-Border Water Management in Transboundary River conflicts in Palestine - Farah, Leila (Journal of Conflict Management, 2024)
Purpose: The aim of the study was to analyze cross-border water management in transboundary river conflicts in Palestine. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on cross-border water management in transboundary river conflicts stresses cooperation, trust-building, and integrated approaches for sustainable solutions. Equitable resource allocation, effective communication among riparian states, and international legal frameworks play vital roles in resolving disputes. Adaptive governance mechanisms are crucial for addressing changing hydrological conditions and political dynamics. Collaborative efforts are essential for managing transboundary river conflicts effectively. Unique Contribution to Theory, Practice and Policy: Hydro-hegemony theory, institutional collective action (ICA) theory & environmental peacebuilding theory may be used to anchor future studies on cross-border water management in transboundary river conflicts in Palestine. Implementing integrated water resources management (IWRM) approaches that involve stakeholders from all riparian countries can enhance practical efforts to address transboundary river conflicts. Developing robust legal and institutional frameworks at both national and international levels is crucial for resolving transboundary river conflicts and promoting cooperation.